Determinanty aktywności edukacyjnej absolwentów - Szłapińska, Joanna; Bartkowiak, Monika (Wydawnictwo Naukowe UAM, 2013)
At present work is perceived as a highly desirable value in which competence is of particular importance. Apart from economic security, a career is to be a source of satisfaction and personal fulfilment for an individual. This situation also results in the fact that a man needs to perceive his career fl exibly, as a peculiar package of alternative professions and a lifelong retraining process. The main focus of this article is to show and emphasize the importance of a multidimensional and continuous educational activity among university graduates in the context of their careers development. The starting point for the discussion on the growing need for adult lifelong learning are the issues of labour market requirements and thus creation of new jobs – the learning organizations. An important aspect presented in this article is the description and analysis of the results of the research on the scope, determinants and prospects of educational activity taken by university graduates in the context of the respondents’ careers. The article ends with the conclusions drawn from the research and the description of the determinants of adults’ educational activity.
Determinants of university graduates’ educational activity
Keywords: career; educational activity; university graduates; lifelong learning; learning organizations